Analysis of thermoregulation indices on microencapsulated phase change materials for asphalt pavement. (30th May 2019) - Ma, Biao; Chen, Sha-sha; Wei, Kun; Liu, Feng-wei; Zhou, Xue-yan
Highlights: Two indexes, latent heat accumulated temperature value (LHATV) and latent heat thermoregulation index (LHTI) were proposed for evaluating the temperature regulation effect of micro-PCMs. Outdoor cube models buried in sufficient temperature sensors to monitor the temperature changes in real time were adopted. The latent heat thermoregulation of micro-PCMs was mainly affected by time and temperature domain. Abstract: Phase change materials (PCMs) can effectively adjust the temperature of asphalt pavement and have broad application prospects. Microencapsulated phase change materials (micro-PCMs) can solve the leaking problem of PCMs, which easily occurs during the heating process of the asphalt mineral mixture. This paper is intended to provide two indices to evaluate the temperature regulation effect of micro-PCMs: the latent heat accumulated temperature value (LHATV) and latent heat thermoregulation index (LHTI). The LHATV reflects the thermal regulation capability of micro-PCMs and the accumulation in temperature difference in a certain time range. The LHTI represents the completion degree of latent heat in unit time and unit temperature, and it reflects the efficiency of latent heat thermoregulation. The outdoor cube model test was conducted on two cube models with dimensions of 30 cm × 30 cm × 30 cm. Each cube model consisted of three asphalt specimens with dimensions of 30 cm × 30 cm × 10 cm. The first cube model, which was mixed with 0.3% wt of micro-PCMs, served as the experimental group, and the other cube model without micro-PCMs addition served as the control group. Inside the two cube models, sufficient temperature sensors were placed to monitor the temperature. The analysis results show that there is a transformable relationship between the latent heat time domain and the temperature domain. In the moderate temperature range and time span, the latent heat thermal stabilization of micro-PCMs can be efficient.